AN ANALYSIS OF ELLIPTICAL CONSTRUCTION MADE BY THE NINTH GRADE STUDENTS OF SMPN 3 SELAT IN ACADEMICC YEAR 2016/2017 - Ni Made Lisma Martarini (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2018)
This present study dealt with An Analysis of Elliptical Construction Made by the Ninth Grade Students of SMPN 3 Selat in Academic Year 2016/2017. This present study was conducted by answering the research question: to what extent is the acquisition of elliptical construction made by the ninth grade students of SMPN 3 Selat ninth in academic year 2016/2017? The aim of the present study here was to analyze of the elliptical construction acquisition made by the ninth grade students of SMPN 3 Selat in academic year 2016/ 2017. The present study made use of ex post facto research design or non experiment research with descriptive analysis. This present study was conducted by recorded the student answer in the test. The investigation was focused on the analysis elliptical sentences made by the subject under study. After got the data the researcher got important result. The result that could be showed as follow: criterion, that (1) there was no one (0%) out of the whole subjects under study showed excellent ability in mastering elliptical construction, (2) there was only 9 subjects (26.47%) of the whole subjects under study showed good ability in mastering elliptical construction, (3) there was 19 subjects (55.88%) of the whole subjects under study showed sufficient ability in mastering elliptical construction, (4) there was 5 subjects (14.70%) of the whole subjects under study showed insufficient ability in mastering elliptical construction, (5) there was only 1 of the subject (2.95%) of the whole subjects under study showed poor ability in mastering elliptical construction. This finding showed that the acquisition of the ninth grade student of SMPN 3 Selat in academic year 2016/2017 in mastering elliptical construction was average. The subject under this study needed to improve their ability to construct the elliptical sentences whether outside or in the classroom because it was very useful for their study.